Patient–provider communication about medication use at the community pharmacy counter. (19th May 2015) - van Dijk, Marloes; Blom, Lyda; Koopman, Laura; Philbert, Daphne; Koster, Ellen; Bouvy, Marcel; van Dijk, Liset
Abstract: Objective: The objectives of this study were to, first, describe the information exchanged between pharmacy staff and patients about prescribed medication at the community pharmacy counter, and second, to investigate to what extent this met professional medication counselling guidelines. Methods: Pharmaceutical encounters were videotaped in four community pharmacies in the Netherlands. Patients were included if they collected a prescription for their own use. An observation protocol, including the MEDICODE checklist, was used to analyse the video recordings. A distinction was made between first and repeat prescriptions. Key findings: One hundred fifty-three encounters were videotaped. When dispensing first prescriptions, pharmacy staff provided most information on instructions how to use the medication (83.3%), form of the medication (71.4%) and treatment duration (42.9%). Topics for repeat prescriptions (such as the effects of the medication and the incidence of observed adverse effects) were rarely discussed. Pharmacy staff rarely encouraged patients to ask questions. Conclusions: Pharmacy staff members provided little medication-related information at the counter, especially for repeat prescriptions, did not encourage active patient participation, and thereby did not adhere to the guidelines of their professional organisation. Further research is needed to understand the reasons for this.